A method for hydrogenating maleic anhydride
Patent Information
- Application Number
- CN202310117617.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-02-15
AI Technical Summary
[0008]针对现有技术的不足,本发明提供一种用于顺酐加氢的方法,采用特定催化剂用于串联的两个反应器进行顺酐加氢反应,该方法具有较高的顺酐转化率和丁二酸酐选择性,可有效解决顺酐深度加氢的问题
Smart Images

Figure BDA0004079112330000071 
Figure BDA0004079112330000081 
Figure BDA0004079112330000082
Abstract
Description
Technical Field
[0001] This invention relates to a method for hydrogenating maleic anhydride, specifically a method for preparing succinic anhydride by hydrogenating maleic anhydride. Background Technology
[0002] Succinic anhydride, also known as succinic anhydride, has the molecular formula C4H4O3. It is a colorless needle-like or granular crystal and is an important organic synthesis raw material, widely used in pharmaceuticals, pesticides, food, petrochemicals, building materials, synthetic resins, dyes, and fine chemicals.
[0003] Currently, the main methods for synthesizing succinic anhydride include bio-fermentation, succinic acid dehydration, and maleic anhydride hydrogenation.
[0004] I. Bio-fermentation is a method that uses microorganisms to ferment corn stalks, sweet potatoes, and starch as the main raw materials to produce succinic anhydride. This process suffers from low product extraction efficiency, low yield and conversion rate, high cost, and the generation of large amounts of wastewater and byproducts, making it difficult to meet the needs of industrial production.
[0005] II. The succinic acid dehydration method involves heating succinic acid in the presence of a dehydrating agent to produce succinic anhydride. However, this method is limited in its widespread adoption due to drawbacks such as high equipment and infrastructure investment, high product cost, unstable quality, high energy consumption during production, and equipment susceptibility to corrosion.
[0006] III. The maleic anhydride hydrogenation method is a technology that uses maleic anhydride as a raw material and selects a highly efficient catalyst for the direct hydrogenation to produce succinic anhydride. This method has the advantages of simple process flow, convenient operation, high equipment utilization, low operating cost, and high product purity, and is currently the most widely used process for producing succinic anhydride in the industrial field. The hydrogenation catalyst systems for the preparation of succinic anhydride from maleic anhydride mainly include noble metal, copper-based, and nickel-based catalysts.
[0007] Currently, the most significant challenge in the maleic anhydride hydrogenation process for preparing succinic anhydride is controlling the depth of hydrogenation. This involves controlling the hydrogenation reaction to the C=C double bond hydrogenation stage, avoiding deep hydrogenation of maleic anhydride, which could lead to the hydrogenation of C=O bonds to generate γ-butyrolactone and water. The water generated from deep hydrogenation can rapidly hydrolyze with succinic anhydride to form succinic acid without a catalyst. Succinic acid is solid in the reaction system, and most of it does not flow out of the reactor with the reactants but adheres to the inside of the catalyst channels, clogging them and reducing catalyst activity and stability. Over time, this increases the bed pressure drop, affecting the stable operation of the apparatus. Deep hydrogenation often occurs in the latter part of the reaction; that is, if two reactors are connected in series, it is more likely to occur in the second reactor; if two catalyst beds are used, it is more likely to occur in the second bed. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention provides a method for the hydrogenation of maleic anhydride. This method employs a specific catalyst in two reactors connected in series to carry out the maleic anhydride hydrogenation reaction. It exhibits high maleic anhydride conversion and succinic anhydride selectivity, effectively solving the problem of deep hydrogenation of maleic anhydride.
[0009] The technical solution adopted in this invention is as follows:
[0010] A method for hydrogenating maleic anhydride, wherein the maleic anhydride feedstock is sequentially passed through a first fixed-bed reactor and a second fixed-bed reactor connected in series, both reactors containing a maleic anhydride hydrogenation catalyst. The maleic anhydride hydrogenation catalyst uses alumina as a support and, based on the total weight of the catalyst, comprises the following components by mass percentage:
[0011] The Ni content is 15%–40%, preferably 20%–35%;
[0012] The Ag content is 0.1% to 5%, preferably 0.5% to 4%;
[0013] The content of silicon-containing organic matter is 0.1% to 6%, preferably 1% to 5%; the silicon-containing organic matter is selected from at least one of methylsilane, dimethyl silicone oil, ethyl silicone oil and phenyl silicone oil, preferably ethyl silicone oil;
[0014] And, the balance is aluminum oxide;
[0015] The catalyst is prepared by the following method:
[0016] Ni and Ag components are loaded into the catalyst according to the agreed ratio, and then silicon-containing organic matter is deposited onto the catalyst surface by vapor deposition.
[0017] Furthermore, the active component Ni and the promoter Ag in the catalyst are simultaneously introduced using a complexation impregnation method. Specifically, ammonia is added to an aqueous solution of nickel chloride and silver chloride to adjust the pH to 11.5–13.8, preferably 12.3–13.5. After stirring until the solutes are completely dissolved, the carrier is impregnated with this solution. The mass ratio of water to carrier is 1:0.8–3, preferably 1:1–2.5. The impregnation time is 0.5–24 hours, preferably 1–6 hours.
[0018] Furthermore, after impregnation, the process includes drying and calcining the catalyst. The drying temperature is 60℃~150℃, preferably 80℃~120℃, and the drying time is 1~24 hours, preferably 2~20 hours. The calcination conditions are: calcination temperature 300℃~800℃, preferably 400℃~700℃, and calcination time 2~24 hours, preferably 4~8 hours.
[0019] Furthermore, the vapor deposition method specifically involves placing the catalyst loaded with the active component in an atmosphere calcination furnace, heating nitrogen gas and introducing it into the liquid silicon-containing organic matter. The hot nitrogen gas carries the vaporized silicon-containing organic matter into the atmosphere calcination furnace for surface treatment of the catalyst. The nitrogen heating temperature is 200℃~450℃, preferably 260℃~400℃; the mass hourly space velocity (HSV) of nitrogen relative to the catalyst is 100 h⁻¹. -1 ~2000h -1 200h preferred -1 ~1500h -1 The catalyst treatment time is 1 hour to 24 hours, preferably 2 hours to 10 hours. The finished catalyst is then obtained.
[0020] Furthermore, the alumina support crystal form is one or more composite types of γ, η or θ types, and the catalyst is strip-shaped or spherical particles. When it is strip-shaped, its cross-section can be cylindrical, clover-shaped or four-leaf clover-shaped, and the diameter of the strip is 0.5 to 3.0 mm, preferably 1.0 to 2.0 mm; when it is spherical particles, its diameter is 0.5 to 5.0 mm, preferably 1.0 to 4.0 mm.
[0021] Furthermore, the specific surface area of the catalyst is 50–300 m². 2 / g, preferably 70-250m 2 / g; pore volume is 0.30-0.80 mL / g, preferably 0.40-0.70 mL / g; average pore diameter is 5-30 nm, preferably 10-25 nm.
[0022] Furthermore, the volume ratio of catalysts packed in the first fixed-bed reactor and the second fixed-bed reactor is 1:0.3 to 4, preferably 1:0.5 to 3.5, and most preferably 1:1.0 to 2.0.
[0023] Furthermore, the conditions for the hydrogenation reaction of maleic anhydride include:
[0024] The reaction conditions for the first fixed-bed reactor are as follows: inlet temperature 30℃~60℃, preferably 35℃~56℃; pressure 2.0MPa~5.0MPa, preferably 2.5MPa~4.5MPa; liquid hourly space velocity (LISH) 2.0 h⁻¹. -1 ~5.0h -1 2.5h is preferred -1 ~4.5h -1 The hydrogen-liquid volume ratio is 10–60:1, preferably 15–38:1.
[0025] The reaction conditions for the second fixed-bed reactor are as follows: inlet temperature 30℃~70℃, preferably 45℃~65℃; pressure 2.0MPa~5.0MPa, preferably 2.5MPa~4.5MPa; liquid hourly space velocity (LHSV) 0.5h⁻¹. -1~3.0h -1 0.8h is preferred -1 ~1.5h -1 The hydrogen-liquid volume ratio is 10–100:1, preferably 35–75:1.
[0026] The maleic anhydride feedstock is a liquid phase feed with γ-butyrolactone as the solvent and a maleic anhydride mass percentage of 4% to 20%, preferably 5% to 17%.
[0027] Furthermore, alternatively, after the maleic anhydride feedstock passes through the first fixed-bed reactor, it is heated to the inlet temperature of the second fixed-bed reactor before entering the second fixed-bed reactor.
[0028] The hydrogenation of maleic anhydride to produce succinic anhydride is a highly exothermic reaction. Typically, two reactors are connected in series with heat extraction in between to control the catalyst bed hotspot temperature below 95°C, preventing deep hydrogenation or self-polymerization of maleic anhydride. However, in actual reactions, trace amounts of maleic anhydride undergo deep hydrogenation to generate water and butyrolactone. This generated water rapidly hydrolyzes with succinic anhydride in the absence of a catalyst to form succinic acid. Succinic acid is solid in the reaction system and most of it does not flow out of the reactor with the reactants but adheres to the inside of the catalyst channels, clogging them and reducing catalyst activity and stability. Over time, this increases the bed pressure drop, affecting the stable operation of the unit. Deep hydrogenation often occurs in the latter part of the reaction; that is, if two reactors are connected in series, it is more likely to occur in the second reactor; if two catalyst beds are used, it is more likely to occur in the second bed.
[0029] In this invention, after the catalyst is treated with silicon-containing organic matter, a hydrophobic group or hydrophobic film in the form of silane is formed on the catalyst surface. This makes it difficult for trace amounts of water generated by deep hydrogenation or carried in the solvent to come into contact with the catalyst surface or enter the catalyst pores. Instead, the water exists in the γ-butyrolactone solvent phase, effectively preventing succinic acid from being generated on the catalyst surface and in the pores and covering the active center or blocking the pores.
[0030] Furthermore, the catalyst uses Ag as a promoter, which isolates Ni atoms, significantly reducing the number of bridging adsorption sites and lowering the Ni electron cloud density. This weakens the adsorption of C=C double bonds, reduces the coverage of maleic anhydride adsorbed species on the surface, promotes the desorption of succinic anhydride, and prevents further hydrogenation. In a preferred embodiment, the catalyst is complexed and impregnated with NH3 as a co-ligand, while the active component Ni and the promoter Ag are loaded onto a support. This results in Ni and Ag species with close spatial positions, allowing for more efficient utilization of the Ag promoter.
[0031] By using two reactors packed with the catalyst in series, combined with the process conditions of this invention, a high maleic anhydride conversion rate and succinic anhydride selectivity can be obtained, while eliminating the negative impacts of deep hydrogenation of maleic anhydride. Detailed Implementation
[0032] The following non-limiting embodiments are intended to enable those skilled in the art to more fully understand the invention, but do not limit the invention in any way.
[0033] In Examples 1-3, maleic anhydride hydrogenation catalysts were prepared (the percentage content of silicon-containing organic matter in the following catalysts was calculated by the difference in raw materials):
[0034] Example 1
[0035] In this embodiment, catalyst A was prepared. By mass percentage, catalyst A contained 30% Ni, 2.5% Ag, 2.3% silicon-containing organic matter, and the remainder was alumina.
[0036] Preparation process: Using strip-shaped alumina with a theta crystal form and a cloverleaf cross-section as a carrier, nickel chloride and silver chloride were placed in a beaker according to a predetermined ratio. Deionized water was added, and then ammonia was added to adjust the pH to 12.5. After stirring until the solutes were completely dissolved, the solution was used to impregnate the carrier. The mass ratio of deionized water to carrier was 1:1.1. After impregnation for 2 hours, the catalyst was dried at 120℃ for 5 hours and calcined at 435℃ for 4 hours. The catalyst was then treated with hot nitrogen gas at 420℃ carrying ethylsilane for 5 hours to obtain the finished catalyst A.
[0037] Example 2
[0038] In this embodiment, catalyst C was prepared. By mass percentage, catalyst C contained 28% Ni, 1.5% Ag, 3.4% silicon-containing organic matter, and the remainder was alumina.
[0039] The preparation process is as follows: Using strip-shaped alumina with a tetraclover-shaped cross-section and η and γ composite crystal forms as a support, nickel chloride and silver chloride are placed in a beaker according to the agreed content, deionized water is added, and then ammonia water is added to adjust the pH value to 12. After stirring until the solutes are completely dissolved, the solution is used to impregnate the support. The mass ratio of deionized water to support is 1:1.2. After impregnation for 2 hours, it is dried at 120℃ for 4 hours and calcined at 450℃ for 5 hours. The catalyst is then treated with hot nitrogen gas at 400℃ carrying methylsilane for 6 hours to obtain the finished catalyst C.
[0040] Example 3
[0041] In this embodiment, catalyst D was prepared. By mass percentage, catalyst D contained 33% Ni, 1.8% Ag, 4.6% silicon-containing organic matter, and the remainder was alumina.
[0042] The preparation process is as follows: Using θ-type spherical alumina as a support, nickel chloride and silver chloride are placed in a beaker according to a predetermined ratio, deionized water is added, and then ammonia is added to adjust the pH to 12.8. After stirring until the solutes are completely dissolved, the solution is used to impregnate the support. The mass ratio of deionized water to support is 1:1.05. After impregnation for 4 hours, the solution is dried at 110℃ for 6 hours and calcined at 440℃ for 6 hours. The catalyst is then treated with hot nitrogen gas at 390℃ carrying ethylsilane for 8 hours to obtain the finished catalyst D.
[0043] Comparative Example 1
[0044] Catalyst B1 was prepared in this comparative example. By mass percentage, catalyst B1 contained 30% Ni, 2.5% Ag, and the remainder was alumina.
[0045] The preparation process is as follows: Using strip-shaped alumina with a theta crystal form and a cloverleaf cross-section as a support, Ni and Ag components are loaded using a conventional impregnation method according to a predetermined content: the support is impregnated with nickel chloride and silver chloride solutions, with a water-to-support mass ratio of 1:1.1 (the Ni component has a larger loading, and its loading is carried out in three steps: each time the support is impregnated with a nickel nitrate aqueous solution containing 1 / 3 of the total Ni, each impregnation lasting 2 hours, followed by drying at 120℃ for 5 hours). After impregnation, it is dried at 120℃ for 5 hours and calcined at 435℃ for 4 hours. The catalyst is then treated with hot nitrogen gas at 420℃ carrying ethylsilane for 5 hours to obtain catalyst B1.
[0046] Comparative Example 2
[0047] Catalyst B2 was prepared in this comparative example. By mass percentage, catalyst B2 contained 30% Ni, 2.5% Ag, and the remainder was alumina.
[0048] The preparation process is as follows: Using strip-shaped alumina with a theta crystal form and a cloverleaf cross-section as a carrier, nickel chloride and silver chloride are placed in a beaker according to a predetermined ratio. Deionized water is added, and then ammonia is added to adjust the pH to 12.5. After stirring until the solutes are completely dissolved, the solution is used to impregnate the carrier. The mass ratio of deionized water to carrier is 1:1.1. After impregnation for 2 hours, the solution is dried at 120℃ for 5 hours and calcined at 435℃ for 4 hours to obtain catalyst B2.
[0049] Example 4
[0050] The catalysts from the above examples and comparative examples were used to carry out maleic anhydride hydrogenation reactions in an evaluation apparatus. Two fixed-bed reactors (reactor A and reactor B) were connected in series, with catalyst loadings of 400 mL and 800 mL, respectively. The feedstock, maleic anhydride, was dissolved in butyrolactone at a mass percentage of 10%.
[0051] The reaction conditions for reactor A are: inlet temperature 52℃, pressure 3.0MPa, and liquid hourly space velocity 3.0h⁻¹. -1 The hydrogen-to-liquid volume ratio is 25:1.
[0052] The reaction conditions in reactor B are: inlet temperature 56℃, pressure 3.5MPa, and liquid hourly space velocity 2.0h⁻¹. -1 The hydrogen-to-liquid volume ratio is 30:1.
[0053] Liquid samples were collected from the outlets of reactors A and B at 200h and 3000h of operation, respectively, for chromatographic analysis. In addition to calculating the maleic anhydride conversion and succinic anhydride selectivity, the main focus was on analyzing the water and γ-butyrolactone content in the samples. Table 1 shows the calculated maleic anhydride conversion and succinic anhydride selectivity at the outlet of reactor A, and the measured water content; Table 2 shows the calculated maleic anhydride conversion and succinic anhydride selectivity at the outlet of reactor B, and the measured water and γ-butyrolactone content.
[0054] Table 1
[0055]
[0056]
[0057] Table 2
[0058]
Claims
1. A method for hydrogenating maleic anhydride, characterized in that, The maleic anhydride feedstock is sequentially passed through a first fixed-bed reactor and a second fixed-bed reactor connected in series. Both reactors contain a maleic anhydride hydrogenation catalyst, which is supported on alumina. Based on the total weight of the catalyst, the active metals and additives, expressed as elements, comprise the following components by mass percentage: The Ni content is 15%~40%. The Ag content is 0.1%~5%, and the silicon-containing organic matter content is 0.1%~6%; the silicon-containing organic matter is selected from at least one of methylsilane, dimethyl silicone oil, ethyl silicone oil, and phenyl silicone oil; And, the balance is aluminum oxide; The catalyst is prepared by the following method: According to the proportion specified in the catalyst, the active component Ni and the auxiliary agent Ag are introduced simultaneously by complexation impregnation: ammonia is added to an aqueous solution of nickel chloride and silver chloride to adjust the pH value to 11.5~13.8, and the solution is stirred until the solute is completely dissolved. The carrier is then impregnated with this solution to load the Ni and Ag components. The silicon-containing organic matter is then deposited onto the catalyst surface by vapor deposition.
2. The method according to claim 1, characterized in that, The catalyst contains 20% to 35% Ni, 0.5% to 4% Ag, and 1% to 5% silicon-containing organic matter; the silicon-containing organic matter is ethyl silicone oil.
3. The method according to claim 1, characterized in that, The mass ratio of water to carrier is 1:0.8~3, and the immersion time is 0.5~24 hours.
4. The method according to claim 1, characterized in that, After impregnation, the catalyst is dried and calcined. The drying temperature is 60℃~150℃ and the drying time is 1~24 hours. The calcination conditions are: calcination temperature is 300℃~800℃ and calcination time is 2~24 hours.
5. The method according to claim 1, characterized in that, The vapor deposition method specifically involves placing a catalyst loaded with active components in an atmosphere roasting furnace, heating nitrogen gas and introducing it into a liquid silicon-containing organic compound, and then using the hot nitrogen gas to carry the vaporized silicon-containing organic compound into the atmosphere roasting furnace to perform surface treatment on the catalyst.
6. The method according to claim 5, characterized in that, The temperature for nitrogen heating is 200℃~450℃.
7. The method according to claim 5, characterized in that, The mass hourly space velocity of nitrogen relative to the catalyst is 100 h⁻¹. -1 ~2000h -1 The catalyst treatment time is 1 hour to 24 hours.
8. The method according to claim 1, characterized in that, The catalyst is in the form of strip-shaped or spherical particles, with the strip-shaped particles having a diameter of 0.5~3.0 mm and the spherical particles having a diameter of 0.5~5.0 mm.
9. The method according to claim 1, characterized in that, The volume ratio of catalysts packed in the first fixed-bed reactor and the second fixed-bed reactor is 1:0.3~4.
10. The method according to claim 1, characterized in that, The maleic anhydride raw material uses γ-butyrolactone as a solvent, and the maleic anhydride mass percentage is 4%~20%.
Citation Information
Patent Citations
Catalyst for continuous production of succinic anhydride from hydrogenation of maleic anhydride and preparation method thereof
CN101502802A